Study on the Influence of Psychological Factors and Sleep Patterns towards Students’ Academic Performance - Gobee, Tarsayini; Khamis, Azme (Enhanced Knowledge in Sciences and Technology, 2025)
Psychological factors and sleep patterns play a major influence on how individuals carry out their personal and academic lives. Psychological health and well-being are greatly impacted by conditions like depression, anxiety, and stress, and cognitive functions that are essential for memory and learning are directly impacted by sleep quality. The purpose of this research is to investigate how psychological factors and sleep quality relate to one another and how this affects university students’ academic performance. Psychological factors and sleep patterns were evaluated using the Depression Anxiety Stress Scales (DASS-21) and Pittsburgh Sleep Quality Index (PSQI) questionnaires. The data was gathered from 150 respondents from Faculty of Applied Sciences and Technology (FAST) at Universiti Tun Hussein Onn Malaysia (UTHM), and the analysis included frequency analysis, chi-square independence testing, and Spearman correlation. The findings showed that a significant number of students suffered from mild to extremely severe stress, anxiety, and depression, even though majority reported normal psychological symptoms. Furthermore, poor sleep quality was reported by 59% of respondents. Additionally, chi-square tests showed an association between anxiety and GPA, as well as anxiety and PSQI. These results were further analysed by correlation analysis, which revealed low correlations between psychological factors and PSQI and high positive correlations among the psychological factors. However, the relationship between academic performance and psychological factor or PSQI was not significant, implying that other factors may influence students’ GPA.